The Effect of Antenatal Yoga on the Level of Anxiety of Pregnant Women in Facing the Labor Process - Warlinda Warlinda (Indonesian Journal of Global Health Research, 2024)
One of the main causes of maternal death is hypertension in pregnancy, which is often triggered by anxiety before childbirth. This study aims to determine the effect of antenatal yoga on the level of anxiety of pregnant women in facing the labor process. Using a quasi-experimental design with a one group design approach, the study involved 30 pregnant women in the third trimester in the Malangke Health Center work area in the period August-September 2024. The sampling technique used total sampling, and the data were analyzed using the Wilcoxon statistical test. The results showed that all respondents experienced a decrease in anxiety levels after the antenatal yoga intervention, with a significant p-value of 0.000 (p <0.05). The average decrease in anxiety had a mean rank of 15.00 and a positive sum of ranks of 435.00. These findings are in line with previous studies which stated that antenatal yoga is effective in reducing anxiety in pregnant women approaching labor. In conclusion, antenatal yoga has a significant effect in reducing anxiety levels in pregnant women, so it can be a recommended intervention to improve the mental health of pregnant women.